Final Reply: When Will Survival Researchers Move Past Defending the Indefensible? - Augustine, Keith (Journal of Scientific Exploration, 2022)
The failure of five psychical researchers to confront my critique of Bigelow Institute contest-winning essays with counterpoints or concessions responsive to its novel criticisms is disappointing. Their defensive and scattershot reply lost sight of whether the critiqued essays met their directive to provide “hard evidence ‘beyond a reasonable doubt’” of the survival of human consciousness. Those who claim that science should expand its metaphysically conservative picture to include things otherwise not known to exist assume the burden of showing what they claim. My interlocutors’ almost exclusively testimonial evidence does not adhere to the long-standing scientific principles required by the scientific community. For the kind of evidence that could be publicly confirmed is simply not the kind that survival researchers have been able to provide, just as we would expect of a hodgepodge of deception, embellishment, malobservation, misreporting, self-deception, and so on; but which would be surprising on the hypothesis that discarnate personal survival occurs. The survival evidence does not even survive elementary scrutiny, let alone outweigh our everyday experience of the biological fragility of our own minds. The totality of the evidence renders discarnate personal survival highly unlikely. Attempts to reinterpret this evidence away through various analogies fail because a hypothesis that makes false predictions, like that of the independence of individual consciousness from a functioning brain, will continue to make them no matter what analogy one uses to illustrate it.